Backbone-Enabled Peptide Macrocyclization through Late-Stage Palladium-Catalyzed C–H Activation - Bai, Zengbing; Wang, Huan (Synlett, 2020)
Peptide macrocycles are widely used in fields ranging from medicinal chemistry to materials science. Efficient chemical methods for the synthesis of cyclic peptides with novel three-dimensional structures are highly desired to facilitate the development of this unique class of compounds. However, the range of methods available for constructing peptide macrocycles is limited compared with that for small molecules. We recently developed new methods for synthesizing highly constrained cyclic peptides with C–C crosslinks through Pd-catalyzed C–H activation reactions. These methods use endogenous backbone amides as directing groups and, therefore, have the potential for use in late-stage functionalization of peptide natural products.
Keywords: cyclic peptides; peptidomimetics; palladium catalysis; C–H activation; macrocyclization; peptide stapling